Quantitative recovery ordered (Q-ROSY) and diffusion: ordered spectroscopy using the spoiler recovery - Anthonsen, Henrik Walbye; Sørland, Geir Humborstad; Zick, Klaus; Sjöblom, Johan; Simon, Sébastien (Diffusion Fundamentals, 2012)
Combined PFG and T1 methods for rapid acquisition of multiple scans of an NMR pulse sequence are presented. The methods apply initially two RF-pulses in combination with two magnetic field gradient pulses of opposite polarity, different strengths and different durations. The basic idea is to spoil any magnetization in any direction before letting the system recover to some degree of restoration of the thermal equilibrium magnetization. Thereafter any pulse sequence can be applied, and the next scan may be run immediately after the end of this spoiler pulse sequence. Thus one avoids the 5 times T1 delay between each scan. The method has been verified at 11.7 Tesla correlating spectral information with T1 or diffusion.